Concordance between a neuroradiologist, a consultant radiologist and trained reporting radiographers interpreting MRI head examinations: An empirical study. Issue 2 (May 2021) - Piper, K.; Mitchell, M.; Griffin, K.; Morgan, T.; Roy, A.; Thomas, A.; Pittock, L.; Woznitza, N.; Faruqui, R.; Sakel, M.
Abstract: Introduction: This study assessed agreement between MRI reporting radiographers and a consultant radiologist compared with an index neuroradiologist when reporting MRI head (brain/internal auditory meati [IAMs]) examinations. The effect on patient management of any discordant reports was also examined. Methods: Two trained MRI reporting radiographers (RRs), a consultant radiologist (CR) and an index neuroradiologist (INR) reported on a random sample of 210 MRI examinations. The radiographers reported during clinical practice and the radiologists in clinical practice conditions. Two independent consultant physicians (neuro-rehabilitation and neuropsychiatry) compared these reports with the index neuroradiologist report for agreement and the clinical importance of discrepant reports. Results: Overall observer agreement between the RRs and CR was comparable in relation to agreement with the INR: RR; 93/210 (44.3%); and the CR; 83/210 (39.4%) for all head MRI examinations (p = 0.32). For brain examinations the difference was similar: RR; 64/180 (35.6%); and CR; 54/190 (30.0%), p = 0.26. Agreement rates for the IAMs examinations were identical, 29/30 (97.7%). For all head MRI examinations (n = 210) there was a very small observed difference of <0.5% in mean agreement between the reporting radiographers and the consultant radiologist (p = 0.92) for examinations where a major disagreement would have been likely to have led to a change in patient management. Conclusion: MRI reporting radiographers reported during clinical practice on MRI head examinations to a level of agreement comparable with a consultant radiologist. Implications for practice: This is an area in which radiographers could provide additional reporting roles to the reporting service to increase capacity. Wider potential benefits include cost-effectiveness and role development/retention of radiographers.